The long limb bones of the StW 573 Australopithecus skeleton from Sterkfontein Member 2: Descriptions and proportions. Issue 133 (August 2019) - Heaton, Jason L.; Pickering, Travis Rayne; Carlson, Kristian J.; Crompton, Robin H.; Jashashvili, Tea; Beaudet, Amélie; Bruxelles, Laurent; Kuman, Kathleen; Heile, Andrea J.; Stratford, Dominic; Clarke, Ronald J.
Abstract: Due to its completeness, the A.L. 288-1 ('Lucy') skeleton has long served as the archetypal bipedal Australopithecus. However, there remains considerable debate about its limb proportions. There are three competing, but not necessarily mutually exclusive, explanations for the high humerofemoral index of A.L. 288-1: (1) a retention of proportions from an Ardipithecus -like chimp/human last common ancestor (CLCA); (2) indication of some degree of climbing ability; (3) allometry. Recent discoveries of other partial skeletons of Australopithecus, such as those of Australopithecus sediba (MH1 and MH2) and Australopithecus afarensis (KSD-VP-1/1 and DIK-1/1), have provided new opportunities to test hypotheses of early hominin body size and limb proportions. Yet, no early hominin is as complete (>90%), as is the ∼3.67 Ma 'Little Foot' (StW 573) skeleton from Sterkfontein Member 2. Here, we provide the first descriptions of its upper and lower long limb bones, as well as a comparative context of its limb proportions. We found that StW 573 possesses absolutely longer limb lengths than A.L. 288-1, but both skeletons show similar limb proportions. This finding seems to argue against a purely allometric explanation for A.L. 288-1 limb proportions. In fact, our multivariate allometric analysis suggests that limb lengths of Australopithecus, as represented by StW 573 and A.L. 288-1, exhibit a significantly different ( p < 0.001) allometric pattern than that which typifies modern humans and African apes. Like some previous analyses, our results also suggest that hominin limb evolution occurred in two stages with: first, a modest increase in lower limb length and a concurrent shortening of the antebrachium between Ardipithecus and Australopithecus, followed by a considerable lengthening of the lower limb along with a decrease of both upper limb elements occurring between Australopithecus and Homo sapiens .